Key concepts & skills for media studies - Clark, Vivienne; Baker, James; Lewis, Eileen (London Hodder Education Publishers, 2002)
This book enables students to master the key concepts and skills involved in today's media studies programs. It contains chapters on How to Read a Media Text, Case Studies, Production Skills and Study Skills, and is complemented by revision tips, glossaries of key terms, useful contacts, research sources and activities.